Aqueous film formation on irregularly shaped inorganic nanoparticles before deliquescence, as revealed by a hygroscopic differential mobility analyzer–Aerosol particle mass system. Issue 6 (2nd June 2016) - Hsiao, Ta-Chih; Young, Li-Hao; Tai, Yu-Chun; Chen, Ke-Ching
ABSTRACT: A hygroscopic tandem differential mobility analyzer (H-TDMA) and a hygroscopic coupled DMA and aerosol particle mass (H-DMA-APM) were coupled to examine aqueous film formation and the deliquescence behavior of inorganic nanoparticles. The two systems complement each other because H-DMA-APM measures mass change, while H-TDMA measures mobility diameter (volume) change of nanoparticles upon water uptake. The former mass change was, in particular, more capable to discern minute particle phase changes than the latter size change at moderate RHs. The mass and diameter changes were used to derive the particle effective density for evaluation of aqueous film formation on the nanoparticle surface before and after deliquescence transition. The measurements further showed that approximately 3–5 and 12–20 monolayer equivalents of water molecules formed on the respective surface of 50- and 100-nm inorganic aerosols (ammonium sulfate and sodium chloride) before deliquescence relative humidity (DRH). These findings support the physical basis of the coated-surface model given by Russell and Ming in 2002, and suggest that the phase transition of inorganic nanoparticles near deliquescence is a gradual process instead of an abrupt change. This phenomenon changed the surface energy values, thus confirming the explanation that the DRH of nanoparticles increases as the particle size decreases. This is the first direct observation of nanoparticle deliquescence phase transition using the H-DMA-APM system, and the detailed characterization of aqueous film formation on inorganic nanoparticles is feasible with the presented measurement systems. © 2016 American Association for Aerosol Research